2010
DOI: 10.1016/j.vetmic.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genetic analysis revealed no predominant new strains of avian infectious bronchitis virus circulating in South China during 2004–2008

Abstract: Twenty-seven strains of avian infectious bronchitis virus (IBV) were isolated from dead or diseased chickens at different chicken farms in South China during 2004-2008, of which the S1 gene was sequenced. Phylogenetic analysis of the S1 gene sequences of the isolated 27 strains together with 29 strains published in Genbank revealed that all IBV strains except for one isolated and one published were clustered into six distinct genotypes I-VI. 26 isolated strains belong to genotypes I, II, and III, forming a big… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 48 publications
(62 reference statements)
4
68
2
Order By: Relevance
“…Most of them belonged to genotype I (Figure 1). This result was consistent with other studies conducted in China (Liu et al, 2006(Liu et al, , 2008(Liu et al, , 2009Xu et al, 2009;Li et al, 2010), which confirms that this genotype is the predominant IBV type circulating in chicken flocks in China. Interestingly, phylogenetic analysis of large numbers of strains of genotype I isolated from 1997 to 2009 in China showed that this type of virus was split in two major phylogenetic clusters, represented by strains LX4 and QX, respectively (Figure 1).…”
Section: Qx-like Ibv (Genosupporting
confidence: 93%
See 3 more Smart Citations
“…Most of them belonged to genotype I (Figure 1). This result was consistent with other studies conducted in China (Liu et al, 2006(Liu et al, , 2008(Liu et al, , 2009Xu et al, 2009;Li et al, 2010), which confirms that this genotype is the predominant IBV type circulating in chicken flocks in China. Interestingly, phylogenetic analysis of large numbers of strains of genotype I isolated from 1997 to 2009 in China showed that this type of virus was split in two major phylogenetic clusters, represented by strains LX4 and QX, respectively (Figure 1).…”
Section: Qx-like Ibv (Genosupporting
confidence: 93%
“…The results of IBV surveillance contrast with the conclusion drawn by Li et al (2010), who reported that no new strains of IBV have circulated in South China in recent years. In the mid-1990s, transmissible proventriculitis, which was associated with IBV infection, was reported both in layer hens and broilers in China (YuDong et al, 1998).…”
Section: Analysis Of Qx-like Ibvs Recently Isolated In China 51contrasting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, while vaccination is the main method for inhibiting IBV in poultry populations [77], its effectiveness on new strains is often minimal, leading to outbreaks in even vaccinated populations [78][79][80]. Perhaps vaccination in conjunction with administering the active polyphenol could have a synergistic effect, similar to that seen when the polyphenol isoquercetin was administered with the influenza medicine amantadine in vitro [24].…”
Section: Discussionmentioning
confidence: 99%